ASSESSMENT OF KNOWLEDGE, ATTITUDE, AND PRACTICE ABOUT PACKAGE INSERTS AMONG MEDICAL UNDERGRADUATE STUDENTS: A CROSS-SECTIONAL QUESTIONNAIRE-BASED STUDY - PRABHA MP, SNEHA; S PRABHAKARAN, SONISH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of our study was to assess knowledge, attitude, and practice regarding package inserts (PIs) among medical undergraduates of a Government Medical College in Kerala, India Methods: A cross-sectional, questionnaire-based study was carried out on 100 medical students. It was conducted with the consent of all participants and after the approval of Institutional Review Board and Ethics Committee. Pre-validated 15 items questionnaire was used to elicit responses about knowledge, attitude, and practice with a scoring scheme of +1 for “yes”/positive response and 0 for “no/I don’t know”/negative response. Data analyzed using “SPSS” and responses were expressed as mean scores and percentages. Results: Statistical analysis (response rate 98%) revealed that 88.2% have seen PIs but only 18.4% had the knowledge of drug acts governing the information to be provided on PIs in India. About 78.6% agreed PIs are necessary add-on to drug information. About 62.2% opined that PIs must be in regional language along with English. About 100% agreed that written information in PIs is difficult to read and understand. About 66.3% feel that doctors must instruct patients to read PIs thoroughly. About 71.4% have referred PIs as a source of knowledge for Indication/Contraindication/ Adverse Effects/Drug interaction. About 95.9% would like to refer PIs in future while prescribing as physician. Conclusion: We conclude that participants have positive attitude toward PIs but have less knowledge as compared with developed countries. Results suggest the need for escalating knowledge and awareness among medical students about PIs which, in turn, help to minimize medication errors.